2020
DOI: 10.4314/as.v19i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slope aspect and position on soil infiltrability in an ultisol in Akwa Ibom State, southern Nigeria

Abstract: Soil infiltrability is an important hydrological process that enhances soil water storage and the minimization of runoff. A study was conducted to evaluate the effect of slope aspect (north, NfS and south, SfS) and positions [(crest (CR), upper (US), middle (MS) and lower (LS)] on soil infiltrability,  that is, initial infiltration rate (io), steady-state infiltration rate (ic) and cumulative infiltration (I), and sorptivity (S) and transmissivity (A) on the University of Uyo Teaching and Research Farm (T&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Consequently, soils on the south slopes tend to be lower in organic matter and are not so deeply weathered. Ogban and Okon (2020) reported that infiltration characteristics were generally higher on north than south aspects.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, soils on the south slopes tend to be lower in organic matter and are not so deeply weathered. Ogban and Okon (2020) reported that infiltration characteristics were generally higher on north than south aspects.…”
Section: Introductionmentioning
confidence: 98%